Trading of Flexibility Products in Multi-DSO and Multi-Scale Electricity Markets. - Paredes-Parrilla, Ángel (UMA Editorial, 2024)
This thesis focuses on the management of flexibility in distribution networks, in particular the integration of distributed energy resources (DERs) and the establishment of local energy markets. The transition to a sustainable and decentralised energy system requires the effective use of flexibility to accommodate the variability of renewable energy and minimise network upgrades. Driven by the shift from centralised dispatch to a decentralised market structure and the increased penetration of DERs such as solar panels and wind turbines, the thesis aims to meet the EU's net zero emissions target for 2050. It addresses the challenges of integrating DERs and managing flexibility, while presenting new business opportunities. The thesis begins with a background, highlighting the factors shaping the transformation of the distribution network: the increase in renewable DERs, new players such as small-scale storage, and the digitalisation of the grid, which requires new tools for flexibility management. It focuses on two main contributions: local market clearing algorithms and DER management for revenue stacking. The first part develops decentralised mechanisms for local markets, defining products and services for efficient flexibility trading. It considers stochastic operating mechanisms to deal with DER uncertainties and promote transparent and fair integration. The second part explores business models that enable flexibility service providers (FSPs) to optimise DER flexibility. It combines revenue streams from different DERs such as demand response, batteries, distributed generation and HVAC systems. Uncertainties associated with the integration of renewables are considered to unlock new revenue streams and promote efficiency.
Operación de productos de flexibilidad en mercados eléctricos Multi-Dso y Multi-Escalares
Overall, the thesis contributes to efficient flexibility management with models, methodologies and market coordination mechanisms. By addressing integration challenges and promoting DER participation, it supports a flexible, sustainable power system. The research aims to improve business opportunities for new market entrants through the effective use of flexibility in multi-scale markets.
Keywords: Energía eléctrica - Distribución - Tesis doctorales; Aggregation; Flexibility; Sustainability; Distributed energy resources; Local markets